A Comparative Study of Sexual Identity and Emotional Disturbance Between Feminine and Masculine Boys - Syed Mustafa, Sharifah Muzlia (1997)
Feminity in males is considered a problem since it has been related significantly with transsexuality and homosexuality. This study attempted to describe and compare the childhood gender-typed interests, current gender identity, sexual orientation, and level of emotional disturbance among feminine boys and masculine boys. Thirty five secondary-school feminine boys were matched with thirty five masculine boys in terms of their age,race, religion and school attended. The feminine boys were purposively selected and objectively identitifed us ing the Feminine Mannerism Checklist. The seventy respondents were administered five scales:seventy respondents were administered five scales: Childhood Gender-typed Interests Scale (CGIS), Feminine Gender Identity Scale (FGIS), Body Image Scale (BIS), Sexual orientation Scale (SOS) and Emotional Disturbance Scale (EDS).